Screening for gestational diabetes mellitus by two step method and the pregnancy outcome: a study in Indian women - Srinivasan, Suguna; Palanisamy, Vijayalakshmi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: In recent times, gestational diabetes is becoming more common Worldwide and complications are seen in fetal development, growth, labour and delivery due to maternal hyperglycemia. Gestational Diabetes Mellitus(GDM) is associated with adverse maternal and fetal outcomes. Among South Asian Population, Indian Women are at high risk of developing carbohydrate intolerance during pregnancy. Hence this study is undertaken to screen for gestational diabetes mellitus by two step method in Indian Women. Methods: This study was done in 153 nondiabetic pregnant women of gestational age 24-28 weeks, excluding diabetes mellitus diagnosed prior to pregnancy. Two step method was followed in the present study and GDM was diagnosed and the pregnancy outcomes were noted. Results: In our study the prevalence of GDM is 8.1% by two step method. Most of the women diagnosed with GDM were of age 26-30 yrs (41.66%). Among the women who were diagnosed as GDM, (58.33%) cases required Insulin along with diet control. In our study 33.33% had vaginal delivery, 8.33% had Emergency LSCS and 58.33% had Elective LSCS. Conclusion: Indian Women have high prevalence of GDM, hence universal screening is essential to diagnose GDM, which will improve the pregnancy outcome.